2019
DOI: 10.2174/1570162x17666190218145048
|View full text |Cite
|
Sign up to set email alerts
|

The Per-1 Short Isoform Inhibits de novo HIV-1 Transcription in Resting CD4+ T-cells

Abstract: Background: Understanding of the restriction of HIV-1 transcription in resting CD4+ Tcells is critical to find a cure for AIDS. Although many negative factors causing HIV-1 transcription blockage in resting CD4+ T-cells have been found, there are still unknown mechanisms to explore. Objective: To explore the mechanism for the suppression of de novo HIV-1 transcription in resting CD4+ T-cells. Methods: In this study, a short isoform of Per-1 expression plasmid was transfected into 293T cells with or without T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…We primarily investigated the influence of BMAL1, REV-ERB, and ROR on HIV-1 replication; however, other circadian factors could also play a role as a Per1 short isoform was shown to inhibit HIV-1 transcription in resting CD4 T cells. 57 …”
Section: Discussionmentioning
confidence: 99%
“…We primarily investigated the influence of BMAL1, REV-ERB, and ROR on HIV-1 replication; however, other circadian factors could also play a role as a Per1 short isoform was shown to inhibit HIV-1 transcription in resting CD4 T cells. 57 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, one of the HIV-1 entry receptors C-X-C chemokine receptor 4 (CXCR4) showed diurnal variation 56 which could result in time-of-day dependent viral entry. We primarily investigated the influence of BMAL1, REV-ERB and ROR on HIV-1 replication, however, other circadian factors could also play a role as a Per1 short isoform was shown to inhibit HIV-1 transcription in resting CD4 T cells 57 .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the nuclear receptor may be involved in induction of amino acid and lipid metabolism, potentially required for recovery from influenza virus infection (39). Per-1, encoded by PER1, is a novel negative regulator of HIV-1 transcription (40). It is suggested that upregulated expression of PER1 regulated influenza virus infection through the same mechanism.…”
Section: Discussionmentioning
confidence: 99%